(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The epitaph of Iulia Benenata (CLEAfr 60; end of 3rd- beginning of 4th cent.), from Makthar, consists of seven hexametres, followed by a post-scriptum. In this paper the verses are examined, where, through Lucretian and Virgilian echoes, afterlife is depicted in pagan terms and the virtuous soul, that stares at hell peacefully (secure), is portrayed as a kind of Lucretian sapiens, free from the fear of death. Moreover, some further data are presented, in order to suggest that the woman might have been a Christian: in particular, the theme of the soul’s staring at hell might be read in light of the Gospel parable of Lazarus and the rich man.